ANALISIS KERUSAKAN JALAN DAN CARA PENANGGULANGANNYA PADA JALAN PROVINSI DI KECAMATAN MUARADUA HINGGA KECAMATAN BUAY RAWAN KABUPATEN OGAN KOMERING ULU SELATAN - Rosyad, Farlin; Suhendra, Alda Beby (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Damage that often occurs on road construction pavement can be caused by an increase in traffic volume on road sections, along with increasing economic growth, with the damage that occurs disrupting people's activities as road users every day. The aim of this research is to find out what types of damage occurred, how much the Pavement Condition Index (PCI) value is and how to overcome the road damage. The methods used in this research are the PCI (Pavement Condition Index) method and the 1995 Directorate General of Highways Standard Repair Method. Jalan Jendral Sudirman OKU Selatan with a length of 2.0 km is divided into 2 segments. Each segment is evaluated by measuring dimensions, identifying the type and level of damage to obtain a PCI value. The research results showed that there were 7 types of damage that occurred on Jalan Jendral Sudirman OKU Selatan, namely, Crocodile Skin Cracks (8.75%), Longitudinal Cracks (6.25%), Transverse Cracks (3.75%), Holes (32, 50%), Grain Release (36.25%), Subsidence (2.50%), and Utility Excavation Filling (10.00%). The average PCI value is 63.25, which shows that the condition of the road pavement is good. As for how to overcome several patterns of damage that occur on Jalan Jendral Sudirman Ogan Komering Ulu Selatan, it can be repaired using the repair method from Binamarga (1995) such as P1 is spreading sand, P2 is asphalting, P3 is closing cracks, P4 is filling cracks, P5 is patching. hole, P6 is Alignment.Keywords: Road Sections, Damage, Pavement Condition Index Method.